A quiet revolution emerging in the fish-farming value chain in Myanmar: Implication for national food security - Belton, Ben; Hein, Aung; Htoo, Kyan; Kham, L. Seng; Nischan, Ulrike; Reardon, Thomas; Boughton, Duncan; International Food Policy Research Institute; Myanmar Development Research Institute, Center for Economic Development (Michigan State University, 2015)
Fish farming (aquaculture) is important to Myanmar’s food security and is developing and transforming quickly. This brief presents findings from a new field survey of the farmed fish value chain that is more detailed and broader than any previous study conducted in Myanmar. Many of our findings are at odds with what we perceive as conventional wisdom about fish farming in Myanmar. The findings have important policy implications to unlock the sector’s full growth potential and food security contributions.